Retrospeksi dan Perspektif Peran Strategis Peneliti Bidang Administrasi dalam Upaya Meningkatkan Kualitas Dan Pemanfaatan hasil penelitian - Sedarmayanti Sedarmayanti (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2005)
Research in administration sector, particularly state administration is one of the functions hold very important role in the efforts to improve the implementation of government towards good governance. Actually the condition of research in state administration sector in Indonesia up to now is considered remain suspended on output point and has not reach the outcome yet. As a matter of fact it is a national cost which is not in proportion with the benefit according to expectation. It is expected that the result of the research should become a better quality result in the future so that it can be used maximally, and can be more useful in providing input for material in making decision properly, either for the sake of administration science development or supporting the administration practitioner in the government’s environment in particular.